Foreign Direct Investment and Economic Growth in India: A Sector-specific Analysis. (March 2019) - Jana, Shib Sankar; Sahu, Tarak Nath; Pandey, Krishna Dayal
The motivation behind this empirical investigation comes from the inconclusive evidence produced by a flurry of previous empirical studies on foreign direct investment (FDI)-growth nexus. The study recognises the fact that the treatment of FDI inflows in an aggregate form instead of a sector-specific approach while correlating it with economic growth remains the most tenuous assumption of the previously conducted studies. Driven by the impetus of filling this gap, this study applies a time-varying parameter model with vector autoregressive specification to examine as to how sector-wise FDI inflows can affect the growth of respective sectors in the context of an emerging economy like India. The study uses a number of econometric tests, such as Johansen's cointegration test, vector error correction model, Granger causality test, variance decomposition analysis and impulse response analysis, to arrive at robust results. The study evidences the inward FDI to be non-contributive to the agricultural output growth. However, a reverse causality is evidenced wherein agricultural output is found to be attracting more FDI into the sector. It also documents interesting evidence for manufacturing sector where the FDI inflow is found to affect its output positively for a couple of years. Regarding service sector, the study confirms a bidirectional causality between FDI and growth both for the short and long run. On the basis of the findings, the study suggests economic policymakers to rejuvenate the primary sector of India so that it can attract and absorb more FDI and ensure sustainable economic growth. Besides, the agriculture-led economic growth policy might be more reliant than service which is largely vulnerable to external shocks.